Treatment and blood pressure control in 47,964 people with diabetes and hypertension: A systematic review of observational studies - McLean, Donna L (Pulsus Group Inc, 2006)
BACKGROUND: Many patients with diabetes also have hypertension, greatly increasing their risk for cardiovascular disease. It has been suggested that hypertension is poorly treated in those with diabetes. OBJECTIVE: To examine treatment and control of hypertension in people with diabetes. DATA SOURCES: Data sources included MEDLINE, EMBASE, HealthSTAR, CINAHL, Web of Science, clinical evidence and government health and statistical Web sites. METHOD: Databases were systematically reviewed and hand searches of the bibliographies of relevant studies (1990 to 2004) were conducted. Two investigators selected studies and extracted the data independently. RESULTS: A total of 44 studies (77,649 subjects with diabetes, 47,964 [62%] of whom also had hypertension) were included. While 83% (range 32% to 100%) of patients with hypertension received drug therapy, only 12% (range 6% to 30%) had their blood pressure (BP) controlled to 130/85 mmHg or less. While BP control rates differed by definition of control (those studies with the least stringent definitions for BP control – 160/90 mmHg or less – reported mean control rates of 37%), treatment and control rates did not differ appreciably between countries or health care settings. CONCLUSIONS: Fewer than one in eight people with diabetes and hypertension have adequately controlled BP, with remarkable uniformity across studies conducted in a variety of settings. There is an urgent need for multidisciplinary, community-based approaches to manage these high-risk patients.